Application of Big Data and Analytics to Increase Competitive Advantage - Eko Siswo Adi Sahputra; Ikhsan Nendi (Publikasi Indonesia, 2024)
In the digital era the volume of data continues to increase rapidly, big data and analytics are important tools for companies to utilize the data and increase competitive advantage. The purpose of this research is to find out how big data and analytics can be applied to increase competitive advantage. This research uses qualitative research methods. The data collection technique in this research is a literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that big data and analytics are important tools for companies to increase competitive advantage in this digital era including through personalization of customer experience, operational optimization, and business strategy development. The implementation of big data and analytics is expected to have an impact on companies so that they can make better decisions, develop new products and services, improve operating efficiency, and strengthen relationships with customers.